2018
DOI: 10.1080/10826084.2017.1413114
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Self-Control is Related to Mental Distress in Patients Entering Substance Use Disorder Treatment

Abstract: Symptoms of mental distress were equally common among patients entering OMT and those entering other inpatient SUD treatment, even if the patients differed on a number of clinical characteristics. Use of alcohol and exposure to violence were associated with more mental distress in both groups. Perceived self-control also appeared to be important when explaining symptoms of mental distress among these SUD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 160 publications
(277 reference statements)
0
10
0
Order By: Relevance
“…In line with recent research [ 34 ] on the predictive relationship between mental health and self-control, the level of mental health symptoms and not variability predicted the subsequent self-control levels. This adds to the current knowledge from cross-sectional studies of substance use populations, where perceived self-control has been found to be associated with mental distress [ 32 , 35 ]. In addition, self-control outperformed mental health variables in predicting craving intensity and relapse status in time-lagged models in this sample, suggesting that self-control plays an important role as both targets for research, monitoring, and intervention.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with recent research [ 34 ] on the predictive relationship between mental health and self-control, the level of mental health symptoms and not variability predicted the subsequent self-control levels. This adds to the current knowledge from cross-sectional studies of substance use populations, where perceived self-control has been found to be associated with mental distress [ 32 , 35 ]. In addition, self-control outperformed mental health variables in predicting craving intensity and relapse status in time-lagged models in this sample, suggesting that self-control plays an important role as both targets for research, monitoring, and intervention.…”
Section: Discussionmentioning
confidence: 94%
“…The role of the affective state on impulsivity has previously been subject to thorough investigations as well as in the substance use population (i.e. [ 32 ]. Evidence suggests that increased mental health symptoms are related to decreased impulse control and hence has a detrimental effect on impulsive behaviors such as substance use [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The summed scale ranged from 0 to 15, with higher scores representing higher severity. The Hopkins Symptom Checklist 25-item version (HSCL-25) [ 36 ] was included as a measure of mental distress [ 37 ]. The version employed in our study used a 5-point Likert-type response format [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mental and behavioral disorders, including SUDs, represent the most common reason for nonparticipation in the Norwegian labor market, accounting for 61% of all disability benefits among young adults in 2015 [ 15 ]. For people in SUD treatment, national unemployment rates are extremely high, ranging from 81 to 91% [ 16 – 19 ]. IPS has been proven effective in Norway for people with moderate and severe mental disorders [ 20 , 21 ] and for young adults at risk of early work disability due to social- and health-related problems [ 22 ].…”
Section: Introductionmentioning
confidence: 99%